Paget–Schroetter syndrome occurring in the nondominant hand - Akina Fukushima; Takaaki Kobayashi; Hayato Kuno; Jiro Hiroki; Akihito Yoshida (Clinical Case Reports, 2023)
Key Clinical Message Paget‐Schroetter syndrome is the primary thrombotic event associated with venous thoracic outlet syndrome. It needs to be suspected when encountering localized brachial swelling and a dilated vein in patients with a history of upper limb exercise.